DIFFERENCES BETWEEN GAAP AND IFRS: IMPLICATIONS FOR INTERNATIONAL INVESTORS IN GLOBAL FINANCIAL ANALYSIS - de Almeida, Alex Porto Alegre (LUMEN ET VIRTUS, 2023)
In an increasingly globalized economy, understanding the differences between accounting standards is essential for investors operating across borders. This paper examines the main divergences between the Generally Accepted Accounting Principles (GAAP) and the International Financial Reporting Standards (IFRS), focusing on how these discrepancies affect financial statement comparability and investment decision-making. Key topics include revenue recognition, asset measurement, treatment of research and development expenses, contingent liabilities, and the presentation of financial statements. Additionally, this study highlights the strategic impact for international investors and discusses the ongoing convergence efforts by the Financial Accounting Standards Board (FASB) and the International Accounting Standards Board (IASB). The paper contributes by reinforcing the importance of accounting literacy for global investment strategies.